The Implementation Of Islamic Law At The Early Spread Of Islam In Indonesian Archipelago - Kasman Bakry; Edi Gunawan (Jurnal Ilmiah Al-Syir'ah, 2018)
The study on the gradualityprinciple (tadarruj) of Islamic law in the context of Islamic law legislation in Indonesia has broad issues. The process of Islamization in the archipelago has been taking place gradually, since the advent of Islam in the 7th century AD or the first century of the emergence of Islam in Arab. The legislation efforts of Islamic law in the context of the legal system of a country always raises two sides, they are universal and the particular. Universality and particularity of the Islamic laware motivated by two dimensions, ie the dimensions of divinity (ilāhiyyah) and the human dimension (insāniyyah). This paper is a qualitative research that focuses on discussing regarding the implementation of Islamic law at the early spread of Islamin the Indonesianarchipelago, with the historically normative approach. The conclusion is the graduality principle has been applied in the legislative process in the Islamic law in Indonesia,but it has no formal legal basis in the form of laws regulating the formation of a national law, although it has been implemented in the legislation process of Islamic law. Keywords: Islamic law; Graduality; legislation; Indonesian Archipelago